Development of Mathematical Physics 1 Module Based on Problem Based Instruction - Yanti, I R; Trisna, S; Ramli, R; Usmeldi, U (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
Mathematical Physics I is one of the courses that train students to think critically and creatively in the learning process. Therefore in this research developed a teaching material in the form of modules based on Problem Based Instruction (PBI). The module began with introduce students to a contextual problem that later ended with the presentation and analysis of student work. This type of research is the development of research using a stage model of Plomp, namely: (1) preliminary research, (2) prototyping phase, and (3) assessment phase.The research subjects involved lecturers and students from two campuses, namely Universitas Negeri Padang and STKIP PGRI West Sumatra. The research data was obtained through the validation sheet of modules that look at the feasibility module by module construction, content and the language used. Item analysis was conducted by using qualitative and quantitative analysis.Based on the results of the validation, results showed that the modules are very valid and ready for trial eligibility to students. Modules that are designed are categorized as very valid with a value of 84.66 and very practical with a practical value of 83.05.This result indicate that developmentof Mathematical Physics I module based on the Problem Based Instruction learning model can be used by students and lectures in learning process.